The Oxford dictionary for writers and editors - The Oxford English Dictionary Department; Collins, F. Howard (Oxford, England : Clarendon Press ; New York : Oxford University Press, 1981)
Everyday words, proper names, and abbreviations have been incorporated to bring the book up to date in matters of vocabulary and usage. Because this is primarily a dictionary of style for written English, guidance on pronunciation has been given only in cases where the reader might otherwise experience difficulty or confusion, and where clarification could not be expected from a normal desk or household dictionary.
Successor to the eleventh edition of Collins' Authors' and printers' dictionary.
ne 24/08/2021
Ref.
Keywords: English language